2023
DOI: 10.5772/intechopen.110379
|View full text |Cite
|
Sign up to set email alerts
|

What is the Point of Assessments?

Abstract: Assessments in higher education remain a crucial method in which the student’s understanding and engagement with the course content continue to be measured. Evidence suggests that effective assessments must not only enhance the student’s learning, but it must also encourage the students to be able to recognize quality as well as improve their performance for future tasks. There are those who argue that because of the emphasis given to employability in the delivery of higher education, assessments are becoming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…The unequal distribution of staff ranks within this study closely resembles the overall composition of Ethiopia's higher education faculty. As of August 2020, national data reported by Adamu (2021) indicated that only 14% of academics held PhDs, whereas 64% possessed master's degrees and 21% bachelor's degrees. The low percentage of female academics (12%) in Ethiopian HEIs (The World Bank, 2021) and the small size in other academic ranks may contribute to this limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The unequal distribution of staff ranks within this study closely resembles the overall composition of Ethiopia's higher education faculty. As of August 2020, national data reported by Adamu (2021) indicated that only 14% of academics held PhDs, whereas 64% possessed master's degrees and 21% bachelor's degrees. The low percentage of female academics (12%) in Ethiopian HEIs (The World Bank, 2021) and the small size in other academic ranks may contribute to this limitation.…”
Section: Discussionmentioning
confidence: 99%